Green Procurement Adoption and Environmental Sustainability: A Study of Public Sector Organizations in South Africa - Ngubane, Zinhle (Global Journal of Purchasing and Procurement Management, 2024)
Purpose: The aim of the study was to investigate the green procurement adoption and environmental sustainability: a study of public sector organizations in South Africa. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study on green procurement adoption in South Africa's public sector indicates a growing awareness and implementation of environmentally sustainable practices. While progress is evident, challenges such as resource constraints persist. Nevertheless, embracing green procurement holds promise for substantial environmental benefits and cost savings. Efforts should focus on further promoting and supporting the adoption of these practices to enhance sustainability in the public sector. Unique Contribution to Theory, Practice and Policy: Institutional theory, diffusion of innovations theory & resource dependence theory may be used to anchor future studies on the green procurement adoption and environmental sustainability: a study of public sector organizations in South Africa. Public sector organizations should invest in capacity-building initiatives to enhance the knowledge and skills of procurement professionals in green procurement practices. Advocate for the development and enforcement of mandatory green procurement regulations and standards by government authorities.